Decision about abortion: itineraries, practices and confidences (Brazilian Journal of Health Research, 2019)
Introduction: Abortion is a persistent practice in Brazil, mainly in regions facing worse socioeconomic conditions and poor access to healthcare. Objective: Analyzing employed abortive practices and the social support to forced gestation interruption (with, or without, fetal loss), based on the experiences of women who decided to have an abortion. Methods: Qualitative research with 7 women, who were selected out of a cohort composed of 742 women. The selected women lived in the region recording the lowest Human Development Index in Espírito Santo State, Brazil. Individual interviews were conducted based on a guide-book. Interviews were recorded, transcribed and cut out in order to allow analyzing the thematic content suggested by Lawrence Bardin. Results: The therapeutic itinerary adopted by the participants in order to make the decision to have an abortion took place in their homes. Most of them used Cytotec®, but some looked for homemade recipes. These women took a silent and stealthy path and confessed to feel guilty about the decision made to stop gestation. Conclusion: These women need to go beyond basic social protection and cultural differences, so that they can be supported by health services that could provide them with spaces for listening, guidance and resolution.